Pengaruh Latihan Agility Terhadap Kecepatan Reaksi dan Kelincahan Atlet Bulu Tangkis - Riskon Halalan Toybah; Sindy Feronika; Patra Christopher Gulo; Ricky Immanuel Tambun; Nimrot Manalu (Universitas Negeri Medan, 2026)
Badminton is a sport that requires agility and footwork for multi-directional movement on the court. This study aims to examine the effect of agility training on the reaction speed and agility of badminton athletes. The research method used was a quasi-experimental with a Pre-test and Post-test design on four UNIMED students. The training applied was the Shadow Footwork cross-path pattern (X-Pattern) which was given for three meetings. Data were analyzed using statistical tests with a significance level of 0.05. The results showed a significant increase in both dependent variables. The average reaction speed (travel time) of athletes increased (became faster) by 8.25%, while the average technical agility score (Body Position, Foot Agility, and Hands) increased by 27.08%. It was concluded that Agility Training (Shadow Footwork H) is effective in improving the reaction speed and movement quality of badminton athletes.